Empowering Digital Entrepreneurship in Technical and Vocational Education and Training (TVET) education - Mastura Mustaffa,; Norngainy Mohd Tawil,; Doris Padmini S. Selvaratnam,; Umawathy Techanamurthy,; Haryanti Mohd Affandi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The article “Empowering Digital Entrepreneurship in Technical and Vocational Education and Training (TVET) Education” embarks on a detailed exploration of the integration of digital entrepreneurship within Technical and Vocational Education and Training (TVET). Utilizing advanced searching techniques across Scopus, WoS, ERIC, and Google Scholar databases, the study synthesizes findings from 34 articles, focusing on four main themes: the overview of TVET education, the impact of digital entrepreneurship on TVET, the issue and challenge in integrating digital entrepreneurship into TVET, and the potential pathways for such integration. This study emphasizes how important it is for TVET institutions to include digital entrepreneurship skills in order to prepare a workforce that can successfully navigate the digital economy. It discusses on the precise balance that needs to be achieved between entrepreneurial digital skills and technical vocational training, highlighting how this synergy is essential to developing creativity, flexibility, and competitiveness in the modern workforce. The study also discusses the difficulties in developing curricula, allocating resources, and the importance of industry-academic collaboration, offering thorough solutions for resolving these issues. This paper significantly advances educational policy and practice by providing an in-depth understanding of how digital entrepreneurship can transform Technical and Vocational Education (TVET) and directing industry and educational stakeholders toward the development of a more dynamic, future-focused vocational training ecosystem